Performance measurement and management control measuring and rewarding performance - Epstein, Marc J.; Manzoni, Jean-François (Emerald, 2008)
In 2001, we gathered a group of researchers in Nice, France to focus discussion on performance measurement and management control. Following the success of that conference, we held subsequent conferences in 2003, 2005, and 2007. This volume contains some of the exemplary papers that were presented at the most recent conference. The conference has grown in number of participants, quality of presentations, and reputation and this year attracted leading researchers in the field from North America, South America, Europe, Asia, Australia, and Africa.Though the conference has been generally focused on performance measurement and management control and has included presentations on many facets of the topic, each year we have also focused on a particular theme of current interest. This year's theme was directed at measuring and rewarding performance. This includes evaluating and rewarding the performance of organizations, units, teams, and individuals. It includes empirical, analytical and experimental research.In addition to the three plenary sessions, this volume also includes some of the other excellent papers presented at the conference. The contents of this book represent a collection of leading research in management control and performance measurement and provide a significant contribution to the growing literature in the area. This collection of papers also covers a representative set of topics, research settings, and research methods. We are hopeful that this book will continue the search for additional understanding and development in performance measurement and management control, and provide guidance for both academic researchers and managers as they work toward improving organizations.
Keywords: Managerial accounting.; elektronické knihy; electronic books